Electrochemical synthesis of poly 4, 4′-methylenedianiline /graphene oxide composite by in situ method as sensitive and selective sensor of thioanisole - Esmail Mohseni; Abdolrasoul Rahmani; Ali Kazemi; Zahra Hamdi (Results in Chemistry)
Background: Sulfur compounds with undesirable properties present in oil and petroleum products have become a global concern, prompting scientists to conduct research into the identification and removal of these compounds. Methods: A voltammetric sensor based on a poly4.4′-methylenedianiline /graphene oxide electrode (PMDA/GO) has been developed for the sensitive and selective detection of thioanisole. The electrosynthesis of the polymer composite was performed by in situ method. No crosslinker was used for polymer synthesis. Non-covalent bonding such as π-π stacking effect between PMDA/GO and thioanisole, made the compact imprinted polymer and imprinted sites.Poly (4.4′-methylenedianiline)/graphene oxide were characterized by Field emission scanning electron microscopy, UV–Vis spectroscopy, Thermogravimetric analysis, Differential thermal analysis and differential scanning calorimetry. By Cyclic voltammetry was also found that the poly PMDA/GO exhibit good specific detection of thioanisol when used as molecular imprinted polymer (MIP) electrodes. Significant findings: The obtained cyclic voltammograms of the MIP electrode showed one irreversible anodic peak at ∼1.5 V. The square wave cathodic current exhibits a linear response to thioanisol over a concentration range of 50(mg L−1) to 200(mg L−1) with a correlation coefficient (R2) of 0.979, a detection limit (LOD) 7 mg L−1 and a quantification limit (LOQ) 26 mg L−1. The proposed method for thioanisole detection shows that the imprinted sensor exhibits improved sensitivity to thioanisole compared to a non-imprinted polymer (NIP).